An Evaluation of the Observer Effect on Treatment Integrity in a Day Treatment Center for Children. (July 2013) - Howard, Monica R.; Burke, Raymond V.; Allen, Keith D.
Treatment integrity is an important concern in treatment centers but is often overlooked. Performance feedback is a well-established approach to improving treatment integrity, but is underused and undervalued. One way to increase its value to treatment centers may be to expose unrealized benefits on the observer who collects the performance feedback data. This "observer effect" could increase the value of performance feedback and promote more consistent evaluation of treatment integrity. The purpose of this investigation was to evaluate the observer effect on treatment integrity. Five supervisors who worked in a day treatment center were asked to collect performance feedback data on staff members' integrity in following a standard treatment protocol that supervisors were also expected to follow. Results showed an immediate and marked improvement in treatment integrity in three supervisors who collected but never received performance feedback. For two supervisors, this effect was reversed and replicated. Implications are discussed.